Home delivery of medication – the role of a patient information leaflet on maximising service uptake. (December 2014) - Watson, L; Ahmed, N; Mccall, H; Minton, J; Benn, P; Edwards, S; Waters, L
There are currently over 30, 000 HIV-positive individuals in London and over 25, 000 on anti-retroviral therapy. In 2009/2010, this equated to £170m spent by London's NHS on anti-retroviral drugs. Ways employed to reduce this cost include standardising the drugs patients are on and delivering medication to patients at home. Home delivery (HD) medication is exempt from value-added tax. The savings made from 10 patients using the home delivery service would free up resources to provide anti-retroviral therapy to one further patient. Studies have shown that concerns surrounding potential breaches of confidentiality are a potential barrier to some people using the home delivery service. In order to challenge these concerns, a leaflet was devised highlighting the major benefits to both the patient and the NHS of home delivery and addressing concerns over confidentiality. The leaflet was handed out to patients at the Mortimer Market Centre who were currently on anti-retroviral medication but not on home delivery. They were asked to complete a survey on their views of the service before and after reading the leaflet, whether they had been previously aware of the service and whether their concerns had been addressed. Some 79% felt that the patient information leaflet addressed all of their concerns, and it helped 11% decide whether to consider using home delivery. However, as more patients were opposed to the service after reading the patient information leaflet than those considering it, more work needs to be done to explore patients' concerns and other factors influencing home delivery service uptake.